Tunes Of Development: An Alternative Lens To Analyse Development (Study Case: Navicula Band Addresses Environmental And Social Problems In Indonesia) - Nisa, Khairun (Indonesian Journal of Development Studies, 2022)
This study aims to describe an alternative approach to analyse development issues by using popular culture as the lens of analysis. Through the analysis of tunes of development, this study argues development should be measured not only through the conventional way of measuring development by economic indicators, primarily measuring GDP (Gross Domestic Products), but also considering culture aspect to achieve a comprehensive measuring of development. Using study case of Navicula Band in its efforts to address environmental and social problems in Indonesia, this study shows an overview about the key to comprehensive development by analysing the society and its culture. This study used qualitative research method and literature review as the data collection technic.